Transesterificação do óleo de coco ariri (Syagrus cocoides Martius) por catálise enzimática: uma abordagem teórica e experimental - LIRA JUNIOR, Carlos Alberto (2025)
The state of Maranhão has several native plant species that can be used to produce vegetable oils, including the ariri coconut palm (Syagrus cocoides Martius). The oil obtained from its fruit (coconut) can be transesterified with specific alcohols and the product applied in the most diverse areas of industry. In view of this potential, the main objective of this study is to investigate the transesterification of coconut ariri oil using the enzymes Amano Lipase PS, from Burkholderia cepacia and Amano Lipase PS-IM (immobilized in diatomaceous earth) as biocatalysts. A review study was conducted to identify methodologies that yield enhanced reaction yields. The study examined the predominant methodologies employed in the enzymatic transesterification reactions of vegetable oils, with a particular focus on the utilization of biocatalysts. The lipases demonstrated notable selectivity and stability under varied reaction conditions were identified as being advantageous over conventional chemical methods due to their reduced environmental impact and enhanced product purity. Concurrently, a concise review was conducted of the predominant computational chemistry methods employed to assess the stability and efficiency of diverse reaction types. This review established the appropriate methodology for evaluating the behavior of each substrate within the reaction medium. Consequently, molecular dynamics (MD) simulations in a mixture of quantum mechanics/molecular mechanics (QM/MM) were employed to investigate the interactions between lauric acid (the primary component of coconut ariri oil) and the active sites of lipases, surrounded by various types of alcohols. Subsequently, experimental tests were conducted to assess the impact of varying oil-to-ethanol molar ratios and catalytic loads (2%, 5%, and 10%) on the ester content obtained. The optimal conditions for this process were determined to be an immobilized lipase from Burkholderia cepacia, a catalytic load of 2%, and an oil/ethanol ratio of 1:4, yielding a maximum of 67.1% of the desired product. Conversely, for lipase in free form, the optimal yields (62.8%) were attained with a catalytic load of 10% and an oil/ethanol ratio of 1:6. These findings underscore the viability of coconut ariri oil as a prospective, eco-friendly substrate for transesterification reactions, underscoring the efficacy of the revised methodologies and computational analyses in optimizing the process.